Tata za zelaznej kurtyny - Rzaczynski, Krzysztof (Poland, 2009)
An exploration of the relationship between father and son. The father in question, classical composer Andrzej Panufnik, died in 1991, and his son Jem, DJ and dance music creator, has always managed to keep a lid on his feelings of loss. Until now.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films